PENGARUH SURAT TEGURAN, SURAT PAKSA DAN SURAT PERINTAH MELAKSANAKAN PENYITAAN TERHADAP PENCAIRAN TUNGGAKAN PAJAK PENGHASILAN ORANG PRIBADI - Umul Maisyaroh (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the effect of the Letter of Reprimand, Forced Letter and Order of Carrying Out Confiscation on the Disbursement of Personal Income Tax Arrears on Surakarta Primary KPP. The type of data used is secondary data with multiple linear regression analysis techniques. The partial test results show the significance value of the Reprimand Letter of 0,234 > 0,05 is not significant. Forced Letter amounting to 0,326 > 0,05 is not significant. A warrant carrying out seizure of 0,001 < 0,05 is significant. While the Simultaneous test results of 0,005 < 0,05 means the Letter of Reprimand, Forced Letter and Order of Carrying Out Seizures together affect the Disbursement of Personal Income Arrears in Surakarta KPP Pratama.